2021
DOI: 10.1111/asap.12269
|View full text |Cite
|
Sign up to set email alerts
|

Social norms misperception among voters in the 2020 US presidential election

Abstract: We aim to explain the dynamics enabling spikes in hate crimes by examining the underlying social‐psychological processes behind it. We see these as captured in empowerment processes among racists who see themselves as “victims” and their position strengthened by majority support from the public for their actions. Building on previous research, we investigated the role social norm misperception (false consensus and pluralistic ignorance), following elections plays as a possible, generally occurring mechanism, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Erisen et al (2021) showed that moral disengagement is positively associated with populist attitudes, especially when they involve a Manichean outlook that conceives of the world (hence, also politics) as a war between light and darkness, or between the good “ordinary people” and the evil immigrants supported by elites. However, what appears as “morally disengaged” is mostly in line with the actors’ ingroup norms (Hoerst & Drury, 2021). Moral disengagement is understood as distancing from moral standards in a specific situation (cf.…”
Section: Populism and Moral Justification Of Political Violencementioning
confidence: 99%
See 2 more Smart Citations
“…Erisen et al (2021) showed that moral disengagement is positively associated with populist attitudes, especially when they involve a Manichean outlook that conceives of the world (hence, also politics) as a war between light and darkness, or between the good “ordinary people” and the evil immigrants supported by elites. However, what appears as “morally disengaged” is mostly in line with the actors’ ingroup norms (Hoerst & Drury, 2021). Moral disengagement is understood as distancing from moral standards in a specific situation (cf.…”
Section: Populism and Moral Justification Of Political Violencementioning
confidence: 99%
“…For instance, Walters et al (2016) discussed the perception of intergroup threats and their concurring emotions (e.g., anger) as a potential determinant of hate crimes. Although the role of negative intergroup emotions (e.g., anger) is frequently discussed in hate crimes in the social psychology literature (e.g., Mackie et al, 2000), positive emotions (e.g., pride) may also trigger aggressive behaviors toward outgroups (e.g., Hoerst & Drury, 2021). Relevant ingroup norms, interests, and values that frame the national pride can then influence what is seen as appropriate and legitimate behavior of the ingroup.…”
Section: Populism and National Pridementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, numerous surveys have found that members of different political groups are not as different in their views as the members believe (Jerit & Zhao, 2020). Moreover, that positions ascribed to others (e.g., Democrats, Republicans) misrepresent their actual opinions, often by exaggerating the extremity of those beliefs (Hoerst & Drury, 2021). By using a social norms approach to demonstrate to individuals the accurate beliefs, positions, and attitudes held by a group of others, it is possible to educate those individuals that the others’ true position is not as discrepant as (falsely) believed.…”
Section: Some Conclusion and Recommendationsmentioning
confidence: 99%